2017
DOI: 10.1093/annonc/mdx182
|View full text |Cite
|
Sign up to set email alerts
|

Copy number alterations assessed at the single-cell level revealed mono- and polyclonal seeding patterns of distant metastasis in a small-cell lung cancer patient

Abstract: Differential protein stability and clinical responses of EML4-ALKfusion variants to various ALK inhibitors in advanced ALK-rearranged non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Thus, M4 seemed derived from the same tumour subclone as the previously developed metastases. The existence of such clones, including very small ones, in different types of cancer matching the distant metastasis profile, was demonstrated by single-cell sequencing experiments including some by our group [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, M4 seemed derived from the same tumour subclone as the previously developed metastases. The existence of such clones, including very small ones, in different types of cancer matching the distant metastasis profile, was demonstrated by single-cell sequencing experiments including some by our group [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mutation profiling detected in 14 paired primary and metastatic tumors of TKI‐naive samples showed that 13 of 14 (92.9%) pairs had identical mutational status. However, higher HS values of KRAS , HER2 , and PIK3CA were observed in metastatic tumors than in unpaired primary tumors, and heterogeneity between primary and metastatic tumors in copy‐number alterations may partly contribute to the differences (Ferronika et al ., ; Sveen et al ., ). Together, these data indicate that although some genes may be involved in clonal divergence, the use of archived primary tumor in molecular diagnosis is feasible to identify the driver mutations of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Tumor heterogeneity is another challenge in using CRISPR/Cas9 technology as a therapeutic tool in cancer patients. Tumors usually contain one or more dominant clones and several minor subclones [7,74,75]. When patients are treated with a specific drug, tumor cell populations go through selection pressure.…”
Section: Discussionmentioning
confidence: 99%